The consensus on rituximab administration in the treatment of patients with rheumatoid arthritis - Szechliński, Jacek; Głuszko, Piotr; Kucharz, Eugeniusz Józef; Maśliński, Włodzimierz; Samborski, Włodzimierz; Tłustochowicz, Witold; Wiland, Piotr (Reumatologia/Rheumatology, 2007)
Rituximab is a biologic B-cell targeted treatment in rheumatoid arthritis. A present consensus statement was formulated in order to determine indications and contraindications of using rituximab in rheumatoid arthritis. This statement was established based on data from randomized controlled trials on haematology and rheumatology. Rituximab in combination with methotrexate constitutes a major advance in the treatment of adult patients with rheumatoid arthritis who have had inadequate response or intolerance of disease modifying anti-rheumatic drugs (DMARDs) including one or more TNF-blocking agents.